PENENTUAN WAKTU BAKU DALAM PEMBUATAN KOTAK ALAT PEMBACA PENGUKURAN MELALUI MOTION STUDY - R. Kiki Abdul Muluk (Sainteks: Jurnal Sain dan Teknik, 2019)
Generally the measurement of standard time is only based on how many product units are produced per unit of time, without regard to the movements carried out by the operator. The movements carried out by the operator in completing the work are very necessary to be evaluated, considering that many of the movements of the operator that are not effective will slow down the completion time of the work, which in turn affects the product output. Movement study is an analysis carried out on several movements of the worker's body in completing work. Through the study of motion the standard time can already be determined by synthesizing the standard times of the parts that have been labeled. Based on the standard time calculation of the results of the motion study, it was obtained the results of 25,988 bowl component units and 84,485 APP lid box components. If 25% of the available time is cut off by the needs of the operator, namely the provision of adjustment factors and the allowance factor for operators of the target of 10,000 APP box units, it is still very possible.